Staatsfonds - neue Akteure an den Finanzmärkten? - Christoph Schalast; Marcel Tiemann; Pascal Tuppi (Frankfurt School of Finance & Management, 2009)
Sovereign Wealth Funds (SWFs) have become active investors on the financial markets. This working paper meets the increasing thirst for information on the investment activities of Sovereign Wealth Funds, their legal environment and the implications on German stock listed corporations. Thus, this paper examines the history of, and reasons for establishing SWFs. Furthermore, concerns regarding transparency and investment activities of SWFs are discussed. The authors find no evidence for politicaly motivated investments or massive market intervention by SWFs. Furthermore, the authors propose that the newly established Santiago Principles will build up trust in the financial markets. The empirical part of the working paper analyzes the impact of SWFs on German stock listed corporations. Main findings of the survey include that corporations lack information on SWFs and disagree with the planned change of the Außenwirtschaftsgesetz. The Survey's results further indicate that participant corporations have no concerns about SWF investment activities. Only few SWFs were willing to participate in the survey and therefore information from the IMF was utilized to get an overview about the sector.
urn:nbn:de:101:1-20090420334
Keywords: F10; F11; F21; F30; G11; G23; K12; K19; K22; 330; Sovereign wealth funds; Staatsfonds; Außenwirtschaftsgesetz; portfolioanalysis; monetary reserve; investment strategy; foreign exchange; transparency; Santiago principles